Prevalence and factors associated with frailty among hospitalized geriatric patients at a tertiary hospital in Egypt - Elsorady, Khalid Elsayed; Al Adrosy, Taha Ibrahim (Medical Journal of Indonesia, 2025)
BACKGROUND Frailty is a geriatric syndrome linked to poor clinical outcomes. Certain diseases and biomarkers may serve as indicators of frailty. This study aimed to assess the prevalence and factors associated with frailty among hospitalized geriatric patients. METHODS This cross-sectional study was conducted on 206 older adults at a tertiary care geriatrics hospital in Egypt. A comprehensive geriatric evaluation was conducted to identify geriatric syndromes. Clinical history and laboratory tests were performed. The clinical frailty scale (CFS) and the mini-mental state examination (MMSE) assessed frailty and cognitive abilities, respectively. Pressure injury (PI) was identified through physical examination. Prehospitalization medications were checked and counted. Polypharmacy was defined as the daily use of ≥5 medications. The Charlson comorbidity index (CCI) was used to determine multimorbidity. Potential frailty biomarkers included red cell distribution width, serum C-reactive protein/albumin ratio, and neutrophillymphocyte ratio. Logistic regression and Spearman’s correlation analyses were performed. RESULTS Frailty was prevalent among 59.2% of the participants and associated with older age, female sex, higher CCI, lower MMSE scores, and lower serum total proteins. Significant geriatric syndromes included dementia, PI, incontinence, polypharmacy, and falls. A history of stroke was a significant comorbidity. Dementia was associated with the highest odds of frailty (odds ratio: 15.695, p<0.001). CFS was negatively correlated with MMSE scores (r = −0.314, p = 0.002) and positively correlated with CCI (r = 0.227, p = 0.003). CONCLUSIONS Frailty is a prevalent geriatric syndrome associated with dementia, falls, multimorbidity, incontinence, PI, malnutrition, and polypharmacy. Novel biomarkers may indicate frailty at mild stages.